2011
DOI: 10.1016/j.jvs.2011.03.217
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome after elective endovascular abdominal aortic aneurysm repair and external validation of a risk prediction model

Abstract: The outcomes of elective EVAR at the RBWH are broadly consistent with those of a nationwide Australian audit and recent randomized trials. Age and ASA score are independent predictors of midterm survival after elective EVAR. The ERA model predicts mortality-related outcomes and initial type I endoleak well for RBWH elective EVAR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 28 publications
4
33
2
4
Order By: Relevance
“…5,[8][9][10][11]15 Chung et al 8 reported that size of the aneurysmal thoracic aorta at the time of first presentation was an independent risk factor for late mortality in patients undergoing thoracic aneurysm repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[8][9][10][11]15 Chung et al 8 reported that size of the aneurysmal thoracic aorta at the time of first presentation was an independent risk factor for late mortality in patients undergoing thoracic aneurysm repair.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Over the recent years in addition to these factors, there is some evidence that preoperative maximal aneurysm size could predict late survival even in the absence of complications or reinterventions for AAA repair. [8][9][10][11] However, this issue has never been addressed as one of more variables within models of multivariate analysis, and it has not been presented in a way that thoroughly discusses the significance of preoperative aneurysm size in late survival. Goal of this article was to identify the relation between preoperative maximal aneurysm diameter and late survival in our study cohort and discuss the implications of this finding.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recent studies have sought to identify pre-operative variables that influence clinical outcomes following EVAR and OSR, to assist surgeons with clinical decision making. 9,10 Most studies, however, have focused on conventional risk factors, such as cardiac and pulmonary risk, without considering the anatomical features of the AAA, including aortic shagginess. Although recent studies suggest possible predictors such as age, female sex, American Society of Anesthesiologists (ASA) score, and chronic obstructive pulmonary disease (COPD), there is a paucity of studies of shaggy aorta in comparison with these classic risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Brountzos et al 33 y AbuRahma et al 34 relacionan la persistencia de la EF2 con el número de colaterales aferentes al saco y la cantidad de trombo intraluminal preoperatorios; otros trabajos refuerzan la importancia del número de colaterales permeables, 19 de su calibre 17,35 y del tamaño de la cavidad de la endofuga 17,35 , incluso con evaluación exclusiva mediante ultrasonografía 3 . En nuestra población algún factor anatómico (número de colaterales) se asoció a la persistencia de la endofuga pero no al crecimiento del saco, lo que sugiere la existencia de subpoblaciones entre las endofugas persistentes cuyo potencial de crecimiento no depende de la anatomía.…”
Section: Discusión Y Conclusionesunclassified